Diagnostic evaluation of risk for bleeding in cardiac surgery with extracorporeal circulation - Damaris Vieira Braga (Revista Latino-Americana de Enfermagem, 2018)
Objective: to identify the risk factors associated with cases of excessive bleeding in patients submitted to cardiac surgery with extracorporeal circulation. Method: case-control study on the factors of risk for bleeding based on the analysis of data from the medical charts of 216 patients submitted to cardiac surgery with elective extracorporeal circulation during a three-year period. Results: variables that are commonly associated with excessive bleeding in studies in the field were analyzed, and the following were considered as risk factors for the nursing diagnosis “risk for bleeding” (00206) in cardiac surgery with extracorporeal circulation: Body mass index lower than 26.35kg/m² (Odds ratio = 3.64); Extracorporeal circulation longer than 90 minutes (Odds ratio = 3.57); Hypothermia lower than 32°C (Odds ratio = 2.86); Metabolic acidosis (Odds ratio = 3.50) and Activated partial thromboplastin time longer than 40 seconds (Odds ratio= 2.55). Conclusion: such variables may be clinical indicators of an operational nature for a better characterization of the risk factor “treatment regimen” and a refinement of knowledge related to coagulopathy induced by extracorporeal circulation, which is currently presumably incorporated into the “treatment regimen” category of the nursing diagnostic classification by NANDA International, Inc.